Harnessing literature in EFL teaching: A case in point - BAYTAR, İlknur; TİMUÇİN, Metin (Cognizance Research Associates, 2021)
Foreign language teaching is a very challenging process and the materials chosen for teaching have of vital importance. In this sense, English teachers’ need for alternative materials to textbooks has been increasing day by day but deciding on the right material to use is a demanding job. Teachers are in a continous search for alternative authentic materials which might enable the learners to see the language in real contexts. It is argued in this study that literary texts, especially short stories, as products of language, can be counted amoung the alternative teaching sources as they provide both the teachers and the learners with abundant source of effective teaching materials on the grounds that literary texts have the potential of reflecting real life events and these texts are likely to increase students’ language and cultural awareness unlike the pseudo narratives. Therefore, this study aims to show how literary text, especially short story genre, can be integrated as a language teaching material in English language teaching classes and to find out the attitudes of the students towards the use of short story in English as a Foreign Language (EFL) setting.
Keywords: 4. Education